Study on corrosion behavior of X65 steel of buried pipeline under dynamic stray current interference - Yilong Chen; Feng Wang; Guohui Zou; Weiqiang Sun; Changchun Li (AIP Advances)
With the construction of a large number of electrified rail transits, the stray current will inevitably affect the nearby buried pipelines. Due to the change in the position of the locomotive in the actual operation process, the direction and magnitude of the stray current constantly change, which made the pipe-to-ground potential of the nearby pipeline fluctuate dramatically. Therefore, this paper studied the corrosion behavior of X65 steel under the action of dynamic interference signals through electrochemical testing and corrosion morphology characterization. The results showed that the analog signal proposed in this paper can effectively characterize the dynamic stray current signal. Different from direct current interference, the non-Faraday process resulted in a power exponential relationship between the open-circuit potential and the peak current under the action of dynamic stray current. Under different peak current densities (0–100 A/m2), the X65 steel was presented in an active corrosion process, controlled by the cathode process. With the increase in the peak current density, the anode control process weakened, at which the corrosion morphology changed from pitting to total corrosion, and the maximum pitting depth was 104.255 μm at 40 A/m2. The final corrosion product at 100 A/m2 was realized as yellow FeOOH on the outer layer and black Fe3O4 on the inner layer.